A república de alunos: projeto pedagógico em ação em busca de uma escola democrática - Silva, Davi do Carmo Ferreira (2013)
This research intends to investigate how the process of elaborating and developing the Pedagogical Project (PP) has functioned at a school on the outskirts of São Paulo. Starting from the presupposition that student participation in the elaboration and development of the Pedagogical Project aids in learning and development as citizens, the objective of this research was to understand the importance of the Student Republic project for the execution and maintenance of the pedagogical project at the state-maintained President Campos Salles Elementary School. Therefore, the specific objectives delineated involved verifying the reasons that the Student Republic was created and whether the project demonstrates a commitment to the principles of the school s PP; student action and the changes provoked by the project; the project s contributions towards democratic practice in the school and the relationship between the Student Republic and the administration of the school, seeking to understand what this relationship demonstrates. This school was chosen as an object of study because it claims to plan, elaborate and develop the PP together with the active participation of the students. The research has used the following authors for its theoretical foundation: Apple (2006), Apple & Beane (2001), Gimeno Sacristán (2001 e 2005), Goodson (2005), Azanha (1998) e Veiga (1995 e 2001). It made use of a qualitative approach with some characteristics of ethnography. The research began with an analysis of the PP and then field research and interviews with different subjects were conducted: the school s director, one pedagogical coordinator, two teachers and six students were involved in this activity, using a flexible interview guide that made it possible to collect any information that could help the research. It was concluded that despite contradictions that exist in the project s reality, the Student Republic meets its objectives of strengthening internal governing bodies, that it is aligned with the principles of the school s PP and that it receives incentive and support from the school administration. It was possible to prove the hypothesis that the effective participation of students in the elaboration and development of the Pedagogical Project, based on democratic administration, collaborates not only in their academic preparation, but also in the increase in their self-esteem and the broadening in their citizenship, including contributing to the maintenance of the school s organization. An innovative project is relevant when it favors student achievement, not only in terms of knowledge, but also in terms of values and norms of conduct